ANALYSIS OF TAX KNOWLEDGE AND TAX SERVICE ON TAX PAYMENT DECISIONS WITH PERCEPTION OF TAX OFFICER CREDIBILITY AS A MODERATING VARIABLES ON TAXPAYERS IN SAMPALI VILLAGE PERCUT SEI TUAN DISTRICT - M. Fadly Azmi; Mesra B; Erwansyah (RADJA PUBLIKA, 2026)
Study This aim For analyze influence knowledge taxes and services tax authorities to decision pay tax with perception credibility officer tax as variables moderation on mandatory tax in Sampali Village , District Percut Sei Tuan. Research This use approach quantitative with sample as many as 85 mandatory selected tax​ through Slovin's formula . Data collected through survey and analyzed use Partial Least Squares (PLS) method . Research results show that knowledge taxes , services tax authorities , and perceptions credibility officer tax influential positive and significant to decision pay tax . In special , perception credibility officer tax play a role as variables strengthening moderation​ influence knowledge tax to decision pay taxes , however No strengthen influence service tax authorities . Findings This give contribution for Directorate General of Taxes in formulate strategies for increase quality service tax authorities and strengthen credibility officer taxes to optimize compliance must tax . Therefore Therefore , it is recommended that the Lubuk Pratama Tax Office Pakam Keep going repair system communication with must taxes , strengthening training professional for officer taxes , as well as increase awareness public about importance compliance tax through various educational programs .